2021
DOI: 10.1038/s41398-020-01126-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic d-ribose and d-mannose overload induce depressive/anxiety-like behavior and spatial memory impairment in mice

Abstract: The effects of different forms of monosaccharides on the brain remain unclear, though neuropsychiatric disorders undergo changes in glucose metabolism. This study assessed cell viability responses to five commonly consumed monosaccharides—D-ribose (RIB), D-glucose, D-mannose (MAN), D-xylose and L-arabinose—in cultured neuro-2a cells. Markedly decreased cell viability was observed in cells treated with RIB and MAN. We then showed that high-dose administration of RIB induced depressive- and anxiety-like behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…Peripheral whole-blood samples were collected from each participant by venous puncture. Consistent with our previous study [ 28 ], serum was isolated by centrifugation at room temperature at 3000 × g for 15 min, aliquoted, and stored at −80 °C until use. Total MANF, EWSR1, and ANXA6 were measured using commercially available high-sensitivity ELISA kits from MEIMIAN (Jiangsu, China) by two blind experimenters.…”
Section: Methodsmentioning
confidence: 93%
“…Peripheral whole-blood samples were collected from each participant by venous puncture. Consistent with our previous study [ 28 ], serum was isolated by centrifugation at room temperature at 3000 × g for 15 min, aliquoted, and stored at −80 °C until use. Total MANF, EWSR1, and ANXA6 were measured using commercially available high-sensitivity ELISA kits from MEIMIAN (Jiangsu, China) by two blind experimenters.…”
Section: Methodsmentioning
confidence: 93%
“…TBX1 is responsible for most of the physical malformations present in 22q11.2 deletion syndrome, or DiGeorge syndrome, which is a congenital disease that has been implicated in various behavioral abnormalities including schizophrenia and other neuropsychiatric/behavioral disorders (69)(70)(71). A recent study also reported that TBX1 in the mouse hippocampus might be linked to monosaccharides-D-ribose-induced depressive-like behavior (72). In the present study, the rare variant rs41298838 was predicted to be highly deleterious to TBX1 function, which made it a potential driving variant for familial depression.…”
Section: Discussion Ogdhl Variant May Be One Of the Major Genetic Fac...mentioning
confidence: 99%
“…Thus, neuronal Tau-protein, α-synuclein, β2-microglobulin, following glycation, contribute to the development of several common neurodegenerative diseases [ 119 , 120 , 121 , 122 , 123 , 124 ]. In addition, cognitive impairments observed in animal models and in diabetic patients has been ascribed to glycation and AGEs accumulation linked to ribose [ 93 , 125 , 126 , 127 , 128 , 129 , 130 ]. Diabetic nephropathy also appears linked to glycation processes and AGEs accumulation [ 131 , 132 , 133 ].…”
Section: The Shady Side Of the Ribose Intakementioning
confidence: 99%